Thirlwall's Law and uneven development under Global Value Chains: A multi-country input-output approach - Andrew B. Trigg (Journal of Economic Structures, 2020)
A notable macroeconomic explanation of uneven development, with particular relevance to developing countries, has been the problem of balance of payments constraints, as captured by Thirlwall's Law: where relative growth rates are explained by differences between income elasticities for exports and imports. Araujo and Lima have formulated a one-country multisectoral disaggregation of this hypothesis using a vertically integrated input-output framework, which is extended here in two main ways. First, international trade in intermediate inputs-the basis for Global Value Chains-is introduced; second, the model is extended to multiple countries. The main outcome of the paper is the development of a new multisectoral method for modelling balance of payments constraints: a Multi-Country Sectoral Thirlwall Law (MCSTL) under which key sector relationships are nested in intercountry trading relationships that encompass both intermediate and final goods. The identification of this input-output structure is developed in analytical stages, moving from a one-country vertically integrated system, to two, three and finally multi-country systems. In addition to its theoretical contribution to understanding the industrial structure of trade, an implication of this multi-country/multi-sector approach is that it can also be tested in future empirical work using the recently available World Input-Output Database of national tables.
Keywords: 330; Uneven development; Thirlwall's Law; Global Value Chains; Input-output analysis; Vertical integration; Trade in value added